‘My work is more necessary than ever’: An Interview With Rick Najera - Warren, Michelle (Latin American Theatre Review, 2018)
Rick Najera speaks candidly about topics near to his heart. Najera discusses some of his past theatrical and comedic ventures, such as his early 2000s Broadway play Latinologues and his stage adaptation of Almost White: Forced Confessions of a Latino in Hollywood at Josefina Lopez’s Casa 0101 theatrical venue. He also explains the importance of his work in CBS’ Diversity Showcase, where he has helped actors and comedians such as Kate McKinnon (Saturday Night Live) and Randall Park (Fresh off the Boat) land mainstream roles. He explains how his work on promoting diverse representation in the media is more necessary than ever in the current U.S. political climate, in which many Latinos feel threatened.